Effect of Oatmeal as Fat Replacer on the Quality of Low Fat Goshtaba Prepared by Traditional and Machine Methods : doi: 10.5958/2581-6616.2021.00009.8 - Jalal, Heena; Salahuddin, Mir; Sofi, A. H.; Wani, S. A.; Pal , M. A.; Hussain , Arshid (Journal of Meat Science, 2022)
The effects of traditional and machine methods of preparation on the quality and acceptability of low-fat Goshtaba formulated with 10% hydrated oatmeal as fat replacer was studied by evaluating them for physicochemical and sensory quality. To achieve this objective, the raw emulsions were prepared by traditional (T) and machine (M) method following the standardized processing protocols and formulations served as controls (T0 and M0) and were modified only to the extent of addition of the 10% hydrated oatmeal as fat replacer and served as treatments (T1 and M1). The results showed that the pH of T1 Goshtaba was higher (P<0.05) than that of T0 whereas pH of M0 and M1 were similar. The emulsion stability of T1 and M1 was better (P<0.05) and that of T1 was better than M1 (P<0.05). The percent cooking yield of T1 and M1 was relatively higher (P>0.05) than that of the controls. The yield of T1 was higher (P<0.05) than M1. The percent moisture of T1 emulsion was higher (P<0.05) than that of T0. The percent moisture of T1 Goshtaba was higher (P<0.05) than that of its control. The percent protein of Goshtaba was higher (P<0.05) under the traditional method. The percent fat of T1 and M1 was higher (P<0.05). The percent ash of T1 Goshtaba was higher (P<0.05) than that of M1. The sensory scores for appearance were similar as also were the scores for flavour as well as juiciness. The trend of these sensory scores was T1>T0>M1>M0. The trend of scores for overall palatability was similar to that of texture viz., T1>M1>T0>M0. These results demonstrated better performance of traditional method of preparation of low fat Goshtaba formulated with 10% hydrated oatmeal.